Hukum dan Globalisasi terhadap Legalitas Ganja Medis - Kartika, Arie; Azwar, Tengku Keizerina Devi (Universitas Medan Area, 2023)
This research aims to analyze the law and the influence of globalization on the legality of medical marijuana. The influence of globalization can play a role in policy change. Countries may be responding to global trends regarding the legalization of medical marijuana and feel the need to follow emerging standards at the international level. In Indonesia itself, the discourse on the legality of medical marijuana has developed, but it has not been regulated in law. This research uses normative legal research methods. Data collection was carried out by literature study and document analysis. The research results show that the background to the legality of medical marijuana is related to a combination of medical, social, economic and political factors. The legalization of medical marijuana involves understanding its potential benefits in medicine as well as changing societal views and legal regulations. There are medical benefits from the cannabinoids found in marijuana, such as THC (tetrahydrocannabinol) and CBD (cannabidiol). That marijuana can help treat several medical conditions, including chronic pain, epilepsy, seizures, and symptoms of other chronic illnesses. In Indonesia, the National Narcotics Agency (BNN) as a government institution strongly rejects the discourse on the legalization of marijuana policy. The legalization of medical marijuana is guided by the bad effects and lack of urgency in the use of this plant. The economic reasons behind the policy of legalizing marijuana are considered wrong because if it is legalized there will be an increase in use and cause accidents which will result in medical and rehabilitation costs.